Mostar 2004: Pilot Workshop - (:unkn) unknown (My University, 1994)
Mostar 2004 Pilot Workshop was held between 25 July and 25 August 1994 at IRCICA in İstanbul.
Brochure titled "Rehabilitation of the Old City of Mostar" published by IRCICA in 2005.
Article titled "Mostar 2004, Celebrate Rebuilding Mostar" published in Arkitekt, no. 403 (1993), 32-33.
Brochure titled "IRCICA and the Bosnia and Hercegovina Connection: The Project for Rebuilding the Multicultural Bosnia and Hercegovina, established in 1992" published by IRCICA.
Wav and Mp3 formats were created from the original audio cassette along with the CD.
Keywords: Mostar-Bosnia and Herzegovina; Old Bridge-Mostar; Architecture-Bosnia and Herzegovina